2017
DOI: 10.21037/hbsn.2016.08.06
|View full text |Cite
|
Sign up to set email alerts
|

Neoadjuvant therapy prior to surgical resection for previously explored pancreatic cancer patients is associated with improved survival

Abstract: Background: Patients with pancreatic ductal adenocarcinoma (PDAC) are frequently referred to tertiary centers after unsuccessful attempted resections at other institutions. The outcome of these patients who are ultimately resected is not well understood. Methods:We performed a retrospective review of patients with PDAC who underwent re-exploration between 1995 and 2013 at a single high volume tertiary care institution. We aimed to evaluate the association of neoadjuvant therapy prior to re-exploration on patho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 40 publications
0
9
0
1
Order By: Relevance
“…Pathologic response generally refers to the analysis of preoperative clinical and postoperative pathologic AJCC/UICC TNM stage. Some studies have attempted to compare outcomes based upon various histopathologic tumor features such as patterns of invasion, grade, and degree of tumor fibrosis 28,42,45,47,56,57 . But, some of these methods have a significant degree of variability as they relate to the effectiveness of NAT.…”
Section: Measures Of Responsementioning
confidence: 99%
See 2 more Smart Citations
“…Pathologic response generally refers to the analysis of preoperative clinical and postoperative pathologic AJCC/UICC TNM stage. Some studies have attempted to compare outcomes based upon various histopathologic tumor features such as patterns of invasion, grade, and degree of tumor fibrosis 28,42,45,47,56,57 . But, some of these methods have a significant degree of variability as they relate to the effectiveness of NAT.…”
Section: Measures Of Responsementioning
confidence: 99%
“…All studies were retrospective reviews, with four conducted using prospectively maintained databases. All but three studies reported the postoperative, pathologic TNM stage 28,56,57 . Four studies chose to report the preoperative clinical stage after the administration of NAT 55,58,60,61 .…”
Section: Measures Of Responsementioning
confidence: 99%
See 1 more Smart Citation
“…Thus, pancreatectomies in patients with PDAC initially assessed as unresectable can be safely performed in a group of patients by surgeons with expertise in pancreatic surgery, in referral surgical centers (33)(34)(35)(36). Neoadjuvant therapy prior to reexploration and resection for initially deemed unresectable PDAC has been recently demonstrated to have a survival benefit (38).…”
Section: Re-exploration and Resection After Initial Diagnosis Of Unrementioning
confidence: 99%
“…G astroduodenopancreatectomia (GDPC) é a cirurgia de escolha para tratamento de cânceres periampulares, sejam eles pancreáticos, ampulares, biliares ou duodenais. Apenas 10 a 20% dos pacientes portadores de tumores periampulares ao diagnóstico tem lesões ressecáveis, devido a tumores localmente avançados ou com doença metastática e, desses, a literatura sugere que de 23 a 30% sejam irressecáveis no momento da cirurgia 1 . A sobrevida desses pacientes está associada com o status de ressecção, o estágio da doença e a localização do tumor 2,3 .…”
Section: Introductionunclassified